"What's in the middle": Scratching beneath the surface of the middle class(es) in Brazil, Côte d'Ivoire, Turkey and Vietnam. (October 2022) - Clément, Matthieu; Rougier, Eric; Berrou, Jean-Philippe; Combarnous, François; Darbon, Dominique
Highlights: Developing countries' (DCs') people who are neither poor nor rich are increasingly categorized as the "middle class". The heterogeneous socio-economic characteristics and subjective preferences of this group are mapped over four countries. DCs' middle-classes share strong and identifying commonalities as to consumption, investment and preference for stability. They also present strong specificities across subgroups that might preclude class identification and stabilization. Knowing better this vulnerable group is urgent to target policies and investment on their socio-economic consolidation. Abstract: The term "middle class" is increasingly used to qualify the mass of people in developing countries who are neither poor nor rich and share consumption patterns historically associated with the western middle class. However, what differentiates them from the ideal-typical middle class, as well as the extent to which emerging middle classes differ across developing countries, has only been marginally documented by economists to date. This article proposes to scratch beneath the surface of the so-called middle-class that is burgeoning in developing countries by documenting the commonalities and differences hidden by the all-encompassing term of "middle class" for a set of developing countries exhibiting different levels of income, economic structures and socio-political systems: Brazil, Côte d'Ivoire, Turkey and Vietnam. Relying on quantitative and qualitative micro-economic data, our paper compares the objective characteristics (occupation, education, income), behavior and subjective expectations of the people standing in the middle of the income distribution in the four countries. Four main research questions structure the paper. Where is the middle? How is the middle specific? Who is in the middle? What does the middle aspire to? Results show that the middle-income group in each country covers distinct realities. Although some similar characteristics and behaviors are observable, our results reveal a strong heterogeneity within each national middle class, with no fewer than four to seven socio-economic subgroups, and strong country-specific traits as most of the subgroups are deeply rooted in the country's specific historical trajectory. In each country, our analysis also unveils a pattern of bipolarization between a rather affluent and stable middle class and a "new" or more vulnerable one. Finally, middle class members appear to be characterized by an individualist positioning and the absence of a marked political commitment, challenging the common assumption that developing countries' middle classes are agents of political change.